(untitled) (Physical Education, Health and Social Sciences, 2025)
Endotracheal suctioning (ETS) is a routine procedure in intensive care units (ICUs) to remove airway secretions in intubated patients. Normal saline instillation (NSI) is still widely practiced, although studies report potential adverse effects such as oxygen desaturation, hemodynamic instability, and increased risk of ventilator-associated pneumonia (VAP). Despite this, NSI continues to be used by respiratory therapists (RTs) in many ICUs, including those in Peshawar, Pakistan. A cross-sectional study was conducted in ICUs of tertiary care hospitals in Peshawar. Thirty respiratory therapists were recruited using a convenience sampling technique. Data were collected through a structured questionnaire and analyzed with SPSS version 22. The study excluded RT trainees and other healthcare professionals to ensure accuracy. Most RTs reported instilling 1–3 ml of normal saline during suctioning, primarily to loosen thick secretions or when clinically indicated, rather than routinely. While 60% stated that NSI did not result in severe complications, adverse effects were reported, including oxygen desaturation, tachycardia, hypertension, increased intracranial pressure (ICP), VAP, bronchospasm, airway irritation, and bleeding. NSI was considered contraindicated in patients with severe airway bleeding. Indicators prompting NSI included excessive secretions and elevated peak inspiratory pressures. Although NSI may facilitate secretion clearance, it can adversely affect patient outcomes and should not be performed routinely. If required, only small volumes (1–3 ml) should be used, and special caution is needed in patients with airway bleeding. Evidence-based suctioning practices are recommended to optimize patient safety and outcomes.